2018
DOI: 10.3390/s18051466
|View full text |Cite
|
Sign up to set email alerts
|

Multiband Envelope Spectra Extraction for Fault Diagnosis of Rolling Element Bearings

Abstract: Bearing fault features are presented as repetitive transient impulses in vibration signals. Narrowband demodulation methods have been widely used to extract the repetitive transients in bearing fault diagnosis, for which the key factor is to accurately locate the optimal band. A multitude of criteria have been constructed to determine the optimal frequency band for demodulation. However, these criteria can only describe the strength of transient impulses, and cannot differentiate fault-related impulses and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…When rolling elements run over the defect area, such as the crack occurring on bearing component, a series of impulses will be generated and thus excite the resonance of the bearing or adjacent components at a certain rate which is called "bearing characteristic frequencies." e vital issue for bearing fault diagnosis is to detect these characteristic frequencies [31].…”
Section: Numerical Simulation and Verificationmentioning
confidence: 99%
“…When rolling elements run over the defect area, such as the crack occurring on bearing component, a series of impulses will be generated and thus excite the resonance of the bearing or adjacent components at a certain rate which is called "bearing characteristic frequencies." e vital issue for bearing fault diagnosis is to detect these characteristic frequencies [31].…”
Section: Numerical Simulation and Verificationmentioning
confidence: 99%
“…Fault detection procedures can be divided into three main categories: signal processing techniques [3]- [6], modelbased techniques [7]- [9], and data-driven ones [10]- [16]. In this work we will focus in the latter, where data will drive the identification of normal and faulty modes of operation.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…There exist several studies focusing on fault diagnosis mostly using vibration data acquired from rotating machinery or rolling-element bearings. For example, it was found by various researchers that envelope analysis is a powerful tool for diagnostics of rolling-element bearing signals [1,2,3]. In [1], authors compared cyclostationary and envelope analysis on vibration data for diagnosing of rolling-element bearings and they reported that envelope analysis is advantageous over cyclostationary analysis (spectral correlation).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, squared envelope analysis was found to be an important method to overcome this problem [2]. A multiband envelope spectral extraction technique was proposed to tackle with determining optimal frequency band for narrow band demodulation using vibration signals for fault diagnosis in [3]. In previous studies it was observed that envelope spectrum is randomly distributed over the frequency.…”
Section: Introductionmentioning
confidence: 99%